Role of Teachers’ Engagement in Student’s satisfaction with Medical College: A Comparison of Private and Public Sector Colleges : Role of Teachers’ Engagement in Student’s Satisfaction - Haris, Sobia; Shah, Beenish; Naqvi, Syeda Saima Qamar; Haris, Muhammad; Deeba, Farah; Khan, Muhammad Jehangir (Pakistan Journal of Health Sciences, 2023)
Student satisfaction is a complex result influenced by the standard of instruction, available resources, the campus community, support services, and the overall atmosphere of the institution. Since teacher engagement has a significant impact on students’ learning experiences, educational institutions should give priority to strategies that increase teacher engagement. Objective: This study investigates the ever-changing elements that impact student satisfaction at our higher education institution by conducting in-depth interviews with a varied range of students. Methods: The sample size kept in the study was 30 (15 from public and 15 from private sector). The researchers utilised thematic analysis to extract significant findings from the participants’ replies to inquiries regarding teaching excellence, available resources, community involvement, support services, and institutional regulations. Results: The results involve the presence of a robust sense of belonging and comprehensive support services, coupled with the various problems encountered by students, offered multifaceted insights into the whole educational journey. It has been examined that teachers have an important and major role in satisfaction of students in both private and public sector. The findings provide useful insights for institutional decision-makers seeking to improve student satisfaction and the overall learning environment. Conclusions: Students’ satisfaction was affected by many complex factors. Customized feedback, a variety of teaching styles, and easier access to specialized resources were suggested, but engaging teaching methods, helpful faculty, and well-equipped resources were praised.